GNG5 Controls the Number of Apical and Basal Progenitors and Alters Neuronal Migration During Cortical Development - Ayo-Martin, Ane Cristina; Kyrousi, Christina; Di Giaimo, Rossella; Cappello, Silvia (Frontiers in Molecular Biosciences, 2020)
Cortical development is a very complex process in which any temporal or spatial alterations can give rise to a wide range of cortical malformations. Among those malformations, periventricular heterotopia (PH) is characterized by clusters of neurons that do not migrate to the correct place. Cerebral organoids derived from patients with mutations in DCHS1 and FAT4, which have been associated with PH, exhibit higher levels of GNG5 expression in a patient-specific cluster of neurons. Here we investigate the role of GNG5 during the development of the cerebral cortex in mice and human cerebral organoids. GNG5, highly expressed in progenitors and downregulated in neurons, is critical for controlling the number of apical and basal progenitors and neuronal migration. Moreover, forced expression of GNG5 recapitulates some of the alterations observed upon downregulation of Dchs1 and Fat4 in mice and human cerebral organoids derived from DCHS1 and FAT4 patients, suggesting a critical role of GNG5 in cortical development.